Application of Guidance Counseling with Cooperative Learning Methods to Increase Middle School Students' Learning Motivation - Sara Sahrazad; Maria Cleopatra; Sigit Widiyarto; Zeinora; Fadjriah Hapsari; Adhis Darussalam Pamungkas; Hugo Aries Suprapto (Formosa Journal of Multidisciplinary Research, 2023)
Cooperative learning is one method that can be applied to the classroom. Cooperative learning carried out together with other students is a method that can increase learning motivation. This type of research is an experiment with a one group pretest post-test design method. The research was conducted on Malidar Middle School students in Bekasi City, class VII in the 2018/2019 semester. The total research sample was 34 students. The data collection technique is to use pre-test and post-test to determine learning motivation. Data were analyzed using the paired t-test, and data normality and homogeneity tests were carried out. The results of the research show that there is an increase in motivation when using the cooperative method. The cooperative learning process begins with group division and the teacher provides case studies which are discussed by the group and presented.